2017
DOI: 10.3390/mi8070228
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nucleic Acid Extraction and Purification Using a Miniature Ultrasonic Technique

Abstract: Miniature ultrasonic lysis for biological sample preparation is a promising technique for efficient and rapid extraction of nucleic acids and proteins from a wide variety of biological sources. Acoustic methods achieve rapid, unbiased, and efficacious disruption of cellular membranes while avoiding the use of harsh chemicals and enzymes, which interfere with detection assays. In this work, a miniature acoustic nucleic acid extraction system is presented. Using a miniature bulk acoustic wave (BAW) transducer ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Following a cleanup step comprising the truncation of barcode and primer sequences, the paired-end reads were merged using FLASH (Magoc and Salzberg, 2011) to obtain raw reads that were later subjected to quality filtering to obtain high-quality clean reads (Bokulich et al, 2013) according to the QIIME quality control process (Caporaso et al, 2010b). To obtain effective tags, the UCHIME algorithm was used to compare the cleaned read sequences with a reference Gold database (Edgar et al, 2011) and thus enable the removal of chimera sequences.…”
Section: Genomic Dna Isolation Sequencing and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Following a cleanup step comprising the truncation of barcode and primer sequences, the paired-end reads were merged using FLASH (Magoc and Salzberg, 2011) to obtain raw reads that were later subjected to quality filtering to obtain high-quality clean reads (Bokulich et al, 2013) according to the QIIME quality control process (Caporaso et al, 2010b). To obtain effective tags, the UCHIME algorithm was used to compare the cleaned read sequences with a reference Gold database (Edgar et al, 2011) and thus enable the removal of chimera sequences.…”
Section: Genomic Dna Isolation Sequencing and Data Analysismentioning
confidence: 99%
“…Quantitative metabolic mapping of the metatranscriptome profiles was performed by mapping the KEGG annotations of identified protein sequences into metabolic pathway maps, using the iPath v2 module (Bokulich et al, 2013). In these maps, the gene expression associated with a metabolic pathway was indicated by the line width, which was determined using the log2 read count values of KEGG-annotated proteins.…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%
“…Several on-chip cell lysis techniques such as chemical lysis ( Ma et al, 2019 ; Yoon et al, 2018 ), mechanical lysis (J. Choi et al, 2015 ; Mahalanabis et al, 2009 ), electrical lysis ( Hügle et al, 2018 ; Kim et al, 2009 ; Nan et al, 2014 ), ultrasonic lysis ( Branch et al, 2017 ), thermal lysis ( Leiske et al, 2015 ; Wang et al, 2011 ; Zhang et al, 2016 ), and enzymatic lysis ( Lounsbury et al, 2013 ; Petralia et al, 2013 ) have been demonstrated for rapid lysis of human and pathogen cells.…”
Section: Introductionmentioning
confidence: 99%
“…For POC applications, solid-phase extraction (SPE) is more widely used for nucleic acid isolation and purification ( Kim et al, 2010 ; Price et al, 2009 ; Reinholt and Baeumner, 2014 ). In SPE, cell lysate is mixed with or passed through solid-phase materials, such as filter papers (R. Tang et al, 2017a ), silica membranes or beads ( Branch et al, 2017 ), polymer resins ( Byrnes et al, 2013 ), organic ligands ( Jin et al, 2017 ), nanomaterials (H. Liu et al, 2018 ), or magnetic particles ( Fu et al, 2018 ; Kang et al, 2017 ; Neto et al, 2017 ) to selectively bind nucleic acids at a pH lower than 7.5 ( Yoon et al, 2018 ), remove impurities, and elute DNA or RNA molecules from the solid phase at a higher pH (~pH 8).…”
Section: Introductionmentioning
confidence: 99%
“…Following sample addition, cell lysis is commonly required to release nucleic acids, however, chemical or enzymatic cell lysis methods can have adverse effects on downstream processes in integrated systems. Branch et al [ 5 ] have evaluated a miniature bulk acoustic wave transducer array to overcome these limitations, and demonstrated extraction efficiencies of nearly 70% in just 10 min.…”
mentioning
confidence: 99%